LINGUISTIC FEATURES OF CITY SLOGANS AS COMMUNICATIVE COMPONENTS OF MODERN SPANISH-LANGUAGE URBAN BRAND COMMUNICATION - Bovsunivska , Alina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the study of theoretical approaches to defining the essence of the concept of "slogan" as a communicative component of urban brand communication. The author, defining the concept of "slogan", emphasizes the pluralism of opinions regarding the specified definition. The article also considers the typological characteristics, functions and requirements for the structure of the slogan. It was determined that the advertising slogan of the city as a microtext is a small text characterized by content and formal integrity, coherence, completeness, expresses a pragmatic instruction and is subordinate to the function of influencing the addressee. The author investigated the linguistic features of city slogans as communicative components of modern Spanish-language urban brand communication.Personal contribution consists in identifying the use of stylistic devices at different levels: phonetic, lexical-semantic, morphological, syntactical during the study of the slogans of Spanish cities.___________References:• Dobrovolska, D. M. «Movni osoblivosti anglomovnih reklamnih sloganiv ta yih vidtvorennya ukrayinskoyu i rosijskoyu movami.» (Dis. kand. filol. nauk, Odesa, 2017), 226.• Shukalo, I. M. Anglomovni metaforichni reklamni slogani ta yih pereklad ukr. movoyu, https://essuir.sumdu.edu.ua/bitstream-download/123456789/25328/1/Shukalo.pdf• Ferrero Paloma Musté.«Análisis lingüístico de un corpus de eslóganes y frases publicitarias de marcas comerciales.»(Tesis doctoral, Universitat Politecnica de Valensia,2015), 380.
Keywords: brand, branding, verbal component, non-verbal component, communicative space, communication, urban brand communication, slogan, information and communication technologies, pragmatics